MAKNA PENDIDIKAN NAHDLATUL WATHAN: TELAAH INTERPRETATIF VISI KEBANGSAAN DAN RELIGIUS: REFLEKSI PEMIKIRAN DAN PERJUANGAN KYAI HAMZANWADI 1904-1997 - Khirjan Nahdi (Educatio, 2009)
This study aims at finding out the meaning of education and education science in Nahdlatul Wathan Institution in the book â€œSejarah Visi Kebangsaan dan Religius: Refeleksi Pemikiran dan Perjuangan Tuan Guru Kyai Haji Muhammad Zainuddin Abdul Madjid 1904-1997). This study is categorized into Historic Research (the history of education) through critical hermeneutics of some (non) written historic sources. Based on the critical analysis results can be understood that early, Nahdhatul Wathan as educational institution is a tool of social reconstruction through religious education because of the social and political conditions in that time. And the further development, Nahdlatul Wathan Education is not only as a tool but also a final object because of education is considered as a need to accumulate the social development. Nowadays, Nahddatul Wathan Education is understood as a tool and final object. In the science of education, the meaning of Nahdlatul Wathan education as a tool and a final object is supported by some components of education science standard, such as foundation and principles, function, content, objective, method, formal and material objects.          Keywords: Meaning of Education